SOME QUESTIONS OF THE ORIGIN OF THE SCYTHIAN COMPLEXES OF ANCIENT FERGANA (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article considers the question of the origin of the Scythian complexes of the Fergana Valley based on the analysis of a wide literary base of researchers. Studying the Scythian complexes, the author reveals a picture of the distribution area of the same Andronovo tribes both in the Zarafshan basin and in the Ferghana Valley. At the same time, the fate of these pastoral tribes is not well known. As the author emphasizes, they gradually dissolved into the environment of local agricultural tribes, or continued their usual occupation - cattle breeding. Judging by the formation of the culture of the Scyths of the Southern Aral Sea region, the author suggests that cattle breeding tribes of the Andronovo culture played a big role in their origin. In the end, the author concluded that steppe tribes, whose culture is similar to the cultures of the Jettisu, the Aral Sea region and the Middle Syr Darya, penetrated Fergana since ancient times. The earliest traces of the steppe circle in the Ferghana Valley are traced in the monuments of the "Kayrakkum culture", the bearers of which are the direct predecessor of the culture of the Scythian tribes.